Molecular phylogeny, historical biogeography and revised classification of andrenine bees (Hymenoptera: Andrenidae) - Pisanty, Gideon; Richter, Robin; Martin, Teresa; Dettman, Jeremy; Cardinal, Sophie (Molecular phylogenetics and evolution, 2022)
[Display omitted] •Aphylogenyis presented for the beesubfamily Andreninae based on UCE sequences.•The Eastern Mediterranean subgenus Cubiandrena is sister to all remaining Andrena.•Many Andrena subgenera exhibit paraphyly or polyphyly, requiring recircumscription.•At least 11 Old World–New World exchange events have occurred within Andrena. The mining bee subfamily Andreninae (Hymenoptera: Andrenidae) is a widely distributed and diverse group of ground-nesting solitary bees, including numerous species known to be important pollinators. Most of the species diversity of Andreninae is concentrated in the mainly Holarctic genus Andrena, comprising ca. 1550 described species. The subfamily and especially the genus have remained relatively neglected by recent molecular phylogenetic studies, with current classifications relying largely on morphological characters. We sampled ultraconserved element (UCE) sequences from 235 taxa, including all andrenine genera and 98 out of 104 currently recognized Andrena subgenera. Using 419,858 aligned nucleotide sites from 1009 UCE loci, we present a comprehensive molecular phylogenetic analysis of the subfamily. Our analysis supports the recognition of seven distinct genera in the Andreninae: Alocandrena, Ancylandrena, Andrena, Cubiandrena, Euherbstia, Megandrena, and Orphana. Within the genus Andrena, present-day subgeneric concepts revealed high degrees of paraphyly and polyphyly, due to strong homoplasy of morphological characters, necessitating a thorough, extensive revision of the higher classification of the genus. Based on our findings, we place the subgenus Calcarandrena in synonymy with Andrena (Lepidandrena); Hyperandrena, Nemandrena, Scoliandrena, Tylandrena and Zonandrena with A. (Melandrena); Distandrena, Fumandrena and Proxiandrena with A. (Micrandrena); Carandrena with A. (Notandrena); Agandrena with A. (Plastandrena); Geandrena and Xanthandrena with A. (Ptilandrena); Xiphandrena with A. (Scrapteropsis); and Platygalandrena and Poliandrena with A. (Ulandrena) (new synonymies). We additionally reestablish the groups known as Opandrena and Truncandrena as valid subgenera of Andrena. Our results also show that the MRCA of Andrena + Cubiandrena dispersed from the New World to the Palaearctic probably during the Eocene–early Oligocene, followed by 10–14 Neogene dispersal events from the Palaearctic to the Nearctic and 1–6 Neogene dispersals back into the Palaearctic, all within the genus Andrena.